Penerapan Artificial Intelligence dalam Sistem Penilaian Otomatis di Bidang Pendidikan dengan Studi Kasus di SMKN 1 Bangkinang - Agus Salim; R. Joko Musridho; Sri Wiji Astuti; Marsa Aulia Hasanah; Putri Cindy Claudia (Journal on Pustaka Cendekia Informatika, 2024)
This study aims to explore the application of Artificial Intelligence (AI) in automated assessment systems in the education sector, with a case study conducted at SMKN 1 Bangkinang. The research is grounded in the growing demand for efficiency and objectivity in evaluating students' learning outcomes, particularly for essays and open-ended responses. Using a quantitative descriptive method and distributing questionnaires to both students and teachers, the findings reveal that most students already utilize AI tools to support their learning, especially in searching for materials and answers. Teachers responded positively to the integration of AI in assessments but emphasized the need for human validation and attention to plagiarism issues. The analysis shows that AI-based evaluation systems, especially those employing Natural Language Processing (NLP), can provide fast and consistent feedback. However, the implementation of such technologies requires proper support and ethical awareness. A hybrid model combining AI capabilities with teacher evaluation is recommended.